2018
DOI: 10.1186/s40813-018-0101-x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of 1-day-old pigs with a porcine reproductive and respiratory syndrome virus (PRRSV) modified live attenuated virus vaccine is able to overcome maternal immunity

Abstract: BackgroundThe objective of the study was to evaluate the influence of maternally derived antibodies (MDA) on the efficacy of a PRRSV-1 based attenuated vaccine, when administered in 1 day-old piglets by the intramuscular route. The protective immunity of the modified live virus vaccine was evaluated in pigs born from seropositive sows, vaccinated at 1 day of age, upon inoculation with a PRRSV-1 isolate. The animals were challenged when the levels of MDAs detected by seroneutralization test (SNT) in the non-vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
(40 reference statements)
0
13
1
Order By: Relevance
“…In Jeong's study, all the piglets were MDA+ at vaccination (no MDA-group included) and thus this precluded to clearly evaluating the impact of MDAs on the vaccine efficacy. As the same, Balasch et al recently showed that vaccination of 1-day-old piglets using a new PRRSV-1 MLV in presence of MDAs induced a partial protection against a challenge at 67 days pv [18]. In Balasch's study, NAs were quantified in piglets at the vaccination time but here also the absence of comparison with vaccinated piglets without MDNAs limits the conclusions of the study.…”
Section: Discussionmentioning
confidence: 77%
“…In Jeong's study, all the piglets were MDA+ at vaccination (no MDA-group included) and thus this precluded to clearly evaluating the impact of MDAs on the vaccine efficacy. As the same, Balasch et al recently showed that vaccination of 1-day-old piglets using a new PRRSV-1 MLV in presence of MDAs induced a partial protection against a challenge at 67 days pv [18]. In Balasch's study, NAs were quantified in piglets at the vaccination time but here also the absence of comparison with vaccinated piglets without MDNAs limits the conclusions of the study.…”
Section: Discussionmentioning
confidence: 77%
“…Due to the fact that the onset of immunity of vaccinated piglets is delayed and usually detectable around 3-4 weeks after vaccination [16], a gap in protection may occur if vaccination is given late in the suckling period or at weaning. In particular, the potential early circulation of PRRSV in piglets after weaning has led to the development of vaccines with an approval for usage from the first day of life for both PRRSV-1 and PRRSV-2 [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we found that a partial heterologous protection was achieved in the absence of detectable NAbs at the challenge time-point. PRRSV has often been reported to induce very low NAb titers which appear late in infection [37,38] or which were even non-detectable upon infection or MLV administration in several cases [39,40,41,42,43,44]. The non-detection could be due to the currently used in vitro techniques which may not capture the neutralization of the virus occurring in vivo.…”
Section: Discussionmentioning
confidence: 99%